Determination of the effect of ethyl pyruvate on the surface contamination of sausage to Listeria monocytogenes by using Q-PCR assay - Cetin, Bayram; Ozkaya, Gulsum Ucak; Uran, Harun; Durak, Muhammed Z. (WILEY, 2019)
In this study, we examined the effect of ethyl pyruvate on the efficacy of the inactivation of Listeria monocytogenes on the surface of sausage samples by using quantitative PCR (Q-PCR). Propidium monoazide (PMA) was used for direct quantification of viable and dead cells. The samples inoculated with L. monocytogenes (3 to 4 log CFU/mL) and uninoculated samples were treated with 0, 42, 105, and 420 mg/L vaporized ethyl pyruvate (EP) in 1 L volume containers. Sausage samples were tested on Days 0, 7, 14, 21, and 28 with regards to changes in microbial, physicochemical, and quality characteristics. As compared with control samples (EP no-applied), 105 and 420 mg/L concentration of vaporized EP applications were provided 1 and 2 log reduction, respectively. The vaporized EP application was considered to be an alternative preservation method for the modified atmosphere and vacuum packaging and could be easily applied, especially in meat products such as sausages. Practical application EP could be used for successful preservation of meat and meat products.
Keywords: ESCHERICHIA-COLI O157H7; STAPHYLOCOCCUS-AUREUS; ALLYL ISOTHIOCYANATE; SALMONELLA SPP.; SPINACH LEAVES; ESSENTIAL OILS; MEAT-PRODUCTS; LACTIC-ACID; SHELF-LIFE; QUALITY; Biotechnology & Applied Microbiology; Food Science & Technology